Factors associated with improved walking in older people during hospital rehabilitation: secondary analysis of a randomized controlled trial - Said, Catherine M; McGinley, Jennifer L; Szoeke, Cassandra; Workman, Barbara; Hill, Keith D.; Wittwer, Joanne E; Woodward, Michael; Liew, Danny; Churilov, Leonid; Bernhardt, Julie; Morris, Meg E (BMC geriatrics, 2021)
Background Older people are often admitted for rehabilitation to improve walking, yet not everyone improves. The aim of this study was to determine key factors associated with a positive response to hospital-based rehabilitation in older people. Methods This was a secondary data analysis from a multisite randomized controlled trial. Older people (n= 198, median age 80.9 years, IQR 76.6- 87.2) who were admitted to geriatric rehabilitation wards with a goal to improve walking were recruited. Participants were randomized to receive additional daily physical therapy focused on mobility (n = 99), or additional social activities (n = 99). Self-selected gait speed was measured on admission and discharge. Four participants withdrew. People who changed gait speed ≥0.1 m/s were classified as ‘responders’ (n = 130); those that changed <0.1m/s were classified as ‘non-responders’ (n = 64). Multivariable logistic regression explored the association of six pre-selected participant factors (age, baseline ambulation status, frailty, co-morbidities, cognition, depression) and two therapy factors (daily supervised upright activity time, rehabilitation days) and response. Results Responding to rehabilitation was associated with the number of days in rehabilitation (OR 1.04; 95% CI 1.00 to 1.08; p = .039) and higher Mini Mental State Examination scores (OR 1.07, 95% CI 1.00 – 1.14; p = .048). No other factors were found to have association with responding to rehabilitation. Conclusion In older people with complex health problems or multi-morbidities, better cognition and a longer stay in rehabilitation were associated with a positive improvement in walking speed. Further research to explore who best responds to hospital-based rehabilitation and what interventions improve rehabilitation outcomes is warranted. Trial registration Australian New Zealand Clinical Trials Registry ACTRN12613000884707; ClinicalTrials.gov Identifier NCT01910740 .